Transcending parallel play: boundary spanning for collective action in wildfire management - Davis, Emily Jane, author; Huber-Stearns, Heidi, author; Cheng, Antony S., author; Jacobson, Meredith, author; MDPI, publisher (Colorado State University. Libraries, 2021)
A key challenge in the United States is how to manage wildfire risk across boundaries and scales, as roles, responsibilities, and ability to act are distributed among actors in ways that do not always incentivize collective action. In this review paper, we provide several conceptual contributions to the understanding of wildfire management through the application of boundary spanning frameworks. This includes: (1) a characterization of four major types of boundaries in managing wildfire risk; (2) a review of major boundary spanning features and frameworks that integrate them; and (3) consideration of current and potential applications of the boundary spanning construct to the domain of wildfire management. Our goal is to advance knowledge of how actors in this arena may overcome "parallel play" to more collectively address wildfire risk. We generate new thinking about wildfire management, and offer potential implications and questions for future research, policy, and management.
Keywords: wildfire management; boundary spanning; risk; collective action